Metabolic responses to isoenergetic meals containing different proportions of carbohydrate and fat. - Whitley, H; Humphreys, S; Samra, J; Campbell, I; Maclaren, D; Reilly, T; Frayn, K (1997)
The purpose of the present study was to investigate the interrelationship between carbohydrate and fat metabolism at rest after isoenergetic meals of varying proportions of carbohydrate and fat. Eight physically-active subjects (BMI 18.1-23.4 kg/m2) were studied at rest on three occasions after an overnight fast. In a balanced design they were given meals containing carbohydrate, protein and fat in the following amounts respectively (g/70 kg body weight): meal 1 121, 16, 48; meal 2 70, 16, 70; meal 3 50, 14, 80. All meals were isoenergetic, containing 4.0 MJ/70 kg body weight, and were of similar appearance. In addition, on a fourth occasion five of the eight subjects consumed meal 4 (g/70 kg body weight): carbohydrate 0, protein 0, fat 108. Blood samples were taken before eating the meal and at intervals following the meal to determine metabolic and hormonal responses. Energy expenditure and substrate oxidation were measured by indirect calorimetry and balance was calculated over the 5 h postprandial period. The incremental areas under the time curves for fat oxidation were greatest after meals 3 and 4 (P < 0.05), whereas incremental areas under the carbohydrate oxidation v. time curves were relatively reduced after these two meals (P < 0.05). This was accompanied by lesser suppression of plasma non-esterified fatty acid concentrations (P < 0.001) and reduced plasma insulin concentrations (P < 0.001) following these meals. Energy balance was almost identical after the three isoenergetic meals. In contrast, there was an inverse relationship between carbohydrate and fat balance following these meals, with carbohydrate balance decreasing as carbohydrate intake decreased and fat balance increasing as fat intake increased. We conclude that there is a close interrelationship between carbohydrate and fat metabolism following isoenergetic meals in resting subjects.